Determinants Influencing the demand for Life Takaful in Malaysia : A Quantitative Study on Income Level, Risk Attitude, and Income Protection (Global Business Management Review (GBMR), 2025)
Life takaful is one of the ways to secure finances for one’s family if the breadwinner dies or experiences total permanent disablement. However, the preference of Malaysians to purchase life takaful is mediocre. This study aims to investigate the determinants of demand for life takaful in Malaysia, focusing on income level, risk attitude, and income protection.  This research involved a total of 196 respondents from Kuala Lumpur, Malaysia, and data collected from questionnaire were analysed quantitatively using Statistical Package for the Social Sciences (SPSS) via descriptive analysis, Analysis of Variance (ANOVA), Correlation and Regression. The results reveal that both risk attitude and income level had significant positive influences on life takaful demand, while income protection produced a negative relationship. Notably, the strongest correlation was found between risk attitude and income level (r = 0.430, p < 0.01), while the weakest was between income level and income protection (r = 0.180, p < 0.05). Despite the uncertainty among respondents about purchasing life takaful, many believed their current coverage was adequate. The findings imply that takaful providers should target individuals with higher income and risk tolerance, while also enhancing educational outreach to improve financial literacy. The contribution of this study lies in its examination of behavioral and financial factors, specifically risk attitude and income protection as underexplored variables in the context of life takaful demand.